Soft parts hydatidosis. - Croci, Fabio; Rocca, Guillermo; dos Santos, Gustavo (Cirugía del Uruguay, 1985)
Soft parts hydatidosis includes localizations in the subcutaneous cellular tissue and skeletal muscle that may be grouped according to their pathogenic, clínica!, evolutive and therapeutic similarities. lncidence of same is very low, very few cases having been reported in our country. Thereby excluding statistical analysis of this pathology at national leve!. This communication contributes nine new cases, and the study of their pathogenic and clinical characteristics, while diagnostic and therapeutic aspects are discussed in the light of present conditions.